The efficacy study of trinity permeation synergism on anti-aging - Ruifang Han; Shuyu Wang; Juntong Li; Meifang Wu; Jian Zhou; Peibiao Zhao; Bin Cui (Journal of Dermatologic Science and Cosmetic Technology, 2024)
Background: More and more consumers are paying attention to skin rejuvenation. However, there is a lack of a non-invasive and efficient solution. Objective: To evaluate the efficacy of a trinity permeation synergism (TPS), which consists of a firming essence, an atomizer and a photoelectric penetrator, for facial anti-aging efficacy. Material and methods: In this work, in vitro cell experiments and human efficacy study were used to evaluate the firming and anti-wrinkle effects. Cell experiments were used to verify the effect of the firming essence on the cell proliferation, migration, and anti-inflammation in keratinocytes (HaCaT), and on the gene expression levels of type I and type III collagen (Col-1 and Col-3) and type I matrix metalloproteinase (MMP-1) in human skin fibroblasts (HSF). After in vitro test, 60 women aged 35–60 years were enrolled in the randomized test, of which 30 subjects were randomly selected to be the experimental group and treated with the TPS system, while the left 30 subjects were treated with the firming essence only considered as control. After 28 days, skin elasticity, skin redness value, and skin wrinkles were measured to evaluate the efficacy of the TPS system. Results: Cell experiments showed that the firming essence can significantly improve the proliferation and the migration of HaCaT cells. It also promoted the expression level of Col-1 and Col-3 gene, and inhibited the expression level of MMP-1 gene in HSF cells. After confirming the efficacy of firming essence, the efficacy benefit of the TPS was further studied. The 28-day tests show that combined use firming essence with atomizer and penetrator can significantly increase skin elasticity, reduce skin hemoglobin value and skin wrinkles on Day 28. Moreover, all the mentioned improvements are significantly better than that in the control group. Conclusion: Through efficient delivery in the whole process, TPS boosts the efficacy of active components in the firming essence. TPS offers an efficient, non-invasive, and convenient way for enhanced facial rejuvenation efficacy.